Penerapan Model Pembelajaran Project Based Learning (PJBL) dalam Meningkatkan Kemampuan Berpikir Kritis Siswa di SD Negeri 15 Ambon - Novenska Lisapaly; Yulinda Berhard; Julian M Lesnussa; Pricilla Walalayo; Riswanto Taniwel; Vera lewerissa (Mathematics Education Study Program, 2025)
This study aims to determine the application of the Project Based Learning (PJBL) learning model in improving students' critical thinking skills at SD Negeri 15 Ambon. The background of this study is the low critical thinking skills of students as seen from the lack of activeness in expressing opinions, asking questions, and solving problems independently. This study uses a qualitative approach with descriptive methods. The subjects of the study were 25 fourth-grade students of SD Negeri 15 Ambon. Data were collected through observation, interviews, and documentation. The results of the study indicate that the application of the PJBL model can improve students' critical thinking skills through the stages of project planning, implementation, and reflection. Students become more active, creative, and able to analyze and solve problems systematically. Thus, the PJBL model is effectively used in the learning process to foster critical thinking skills of elementary school students.